Fatique effects in maximal ergometer rowing - Smith, R.; Milburn, P. (Proceedings of the First Australasian Biomechanics Conference, 1996, Sydney, 1996)
This study analysed the MEE of 5 national level and 5 club level female rowers during a six minute maximal effort with the purpose of investigating the source of changes in performance over time that may be related to the distribution of mechanical energy fractions. Result: The cost of maximal ergometer rowing in MEE terms increases with time for the sample of rowers tested in this study. This was due mainly to an increase in the accelerations of the body segments and due, only to an insignificant extent, to a decrease in energy saved through transformations. Loss of concentration and other effects of muscular fatigue may have had an effect on the control of rowing technique which resulted in the less economical movement patterns observed in this study. (from: Proceedings of the First Australasian Biomechanics Conference; ISBN 0 86758 999 X))